Cervical Spinal Meningeal Melanocytoma Presenting as Intracranial Superficial Siderosis - Savitha Srirama Jayamma; Seema Sud; TBS Buxi; VS Madan; Ashish Goyal; Shashi Dhawan (Case Reports in Radiology)
Meningeal melanocytoma is a rare pigmented tumor of the leptomeningeal melanocytes. This rare entity results in diagnostic difficulty in imaging unless clinical and histopathology correlation is performed. In this case report, we describe a case of meningeal melanocytoma of the cervical region presenting with superficial siderosis. Extensive neuroradiological examination is necessary to locate the source of the bleeding in such patients. Usually, the patient will be cured by the complete surgical excision of the lesion.